3D-Reconstruction of a Giant Posidonia oceanica Beach Wrack (Banquette): Sizing Biomass, Carbon and Nutrient Stocks by Combining Field Data With High-Resolution UAV Photogrammetry - Tomasello, Agostino; Bosman, Alessandro; Signa, Geraldina; Rende, Sante Francesco; Andolina, Cristina; Cilluffo, Giovanna; Cassetti, Federica Paola; Mazzola, Antonio; Calvo, Sebastiano; Randazzo, Giovanni; Scarpato, Alfonso; Vizzini, Salvatrice (Frontiers in Marine Science, 2022)
Beach wracks are temporary accumulations of vegetal detritus that can be found along coastlines all over the world. Although beach wracks are often perceived as a nuisance for beach users, they play a crucial ecological role in carbon and nutrient connectivity across ecosystem boundaries, especially when they reach a relevant size, as in the case of the wedge-shaped seagrass accumulations called banquette. In this study, three-dimensional mapping of a giant Posidonia oceanica banquette was carried out for the first time using high-resolution UAV photogrammetry combined with field sampling and compositional and chemical analysis. The combined approach allowed a reliable estimation of the amount and spatial distribution of both vegetal biomass and sedimentary mass, as well as of total carbon, nitrogen and phosphorus content, revealing that i) banquette act as a sediment trap and represent hot spots of seagrass biomass and carbon accumulation; ii) banquette thickness, rather than the distance from the sea, influences the spatial distribution of all variables. Moreover, high-resolution digital elevation models (DEM) revealed discontinuous patterns in detritus accumulation resulting in an unknown banquette type here termed “Multiple Mega-Ridge banquette” (MMR banquette). On the one hand, this study highlighted the high potential of the UAV approach in very accurately 3D mapping and monitoring of these structures, with relevant implications for ecosystem service estimation and coastal zone management. On the other hand, it opened new questions about the role played by temporary beach wracks and, in particular, by P. oceanica banquette in the blue carbon exchange across land-ocean boundaries.